ANALISIS PENGARUH PROPORSI FLY ASH BATU BARA SEBAGAI BAHAN POZZOLAN TERHADAP WORKABILITY BETON NORMAL - Helia Dewi, Nur Afni; Gunasti, Amri (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2025)
The use of coal as fuel for the Paiton Steam Power (PLTU) produces waste in the form of fly ash and bottom ash. Fly ash contains a high amount of calcium oxide, which give it pozzolanic properties when it reacts with water. The use of fly ash as an additive in concrete or as a partial replacement for cement has been widely developed. The aim of this research is to determine the effect of adding coal fly ash on the slump value of normal concrete. Five variations of samples were tested, each with three replicates, namely normal concrete (0% fly ash) and mixtures of 5%, 10%, 15%, and 20% fly ash. The type of fly ash used is type C from the Paiton Steam Power. Material characteristic testing was conducted on coarse aggregates, fine aggregates, and fly ash. The slump test results were statistically analyzed using a one-way ANOVA method to determine whether there were significant differences among the groups. The highest slump value was observed in the 15% fly ash variation, which reached 120 mm, while the statistical test indicated a significant difference in the addition of fly ash to the concrete slump value with a significance value or p-value of 0.000 (<0.05).